Globalization of food systems in developing countries : impact on food security and nutrition. - Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 2004)
Food systems are being transformed at an unprecedented rate as a res ult of global economic and social change. Urbanization, foreign direct investment in markets of developing countries, and increasing incomes a re prime facilitators, while social changes such as the increased numbe r of women in the workforce and rural to urban migration, provide added stimulus. Changes are also facilitated by food production based on int ensive agriculture, new food processing and storage technologies, longe r product shelf-life, the emergence of food retailers such as fast food outlets and supermarkets and the intensification of advertising and ma rketing of certain products. The sum of these changes has resulted in d iverse foods that are available all year for those who can afford them, as well as a shift in home-prepared and home-based meals to pre-prepar ed or ready to eat meals, often consumed away from home. These food sys tem and lifestyle changes are in turn having an impact on the health an d nutritional status of people in developing countries. There is an ind ication of rapid increases in overweight and obesity and an increasing prevalence of diet-related non-communicable diseases.
The papers appearing in this publication were first presented at the workshop "Globalization of food systems: impacts on food security and nutrition" held at FAO headquarters in Rome from 8 to 10 October 2003.
"TC/M/Y5736E/1/11.04/1200"--P. [4] of cover.
Includes bibliographical references.
Keywords: World health -- Congresses; Food supply -- Developing countries -- Congresses; Nutrition -- Developing countries -- Congresses